A Microalgae-Methanotroph Coculture is a Promising Platform for Fuels and Chemical Production From Wastewater - Wang, Jin; Roberts, Nathan; Hilliard, Matthew; He, Q. Peter (Frontiers in Energy Research, 2020)
Wastewater resource recovery facilities are major energy consumers in a community, as well as major contributors for greenhouse gas (GHG) emission. Although anaerobic digestion (AD) is widely employed in wastewater treatment to reduce the amount of solid organic waste and the sludge produced, the use of the produced biogas is mostly limited to heating and electricity generation, while the nutrient rich digestate still requires further treatment. In this work, we propose a waste-to-value (W2V) platform based on a microalgae-methanotroph coculture, which can convert AD-generated biogas into value-added products, while simultaneously removing nutrients from digestate. The platform takes advantage of the synergistic interactions within a microalgae-methanotroph coculture to achieve significantly improved productivity of microbial biomass and enhanced nutrient recovery performance. Using Chlorella sorokiniana – Methylococcus capsulatus (Bath) as the model coculture, we demonstrate that the coculture offers a highly promising platform for W2V technologies, which can efficiently recover energy (from CH4) and carbon (from both CH4 and CO2) to produce microbial biomass, while removing nutrients from wastewater to produce treated clean water. Compared to microalgae monoculture, the coculture achieved 120% improvement in biomass production, 71% and 164% improvement in total nitrogen and total phosphorous removal respectively, when the same amount of biogas was provided.